Clinical factors associated with functional outcomes in patients with single subcortical infarction with neurological deterioration - Yang, Yi; He, Yue; Han, Wei; Xu, JianHui; Cai, ZhiRong; Zhao, Tian; Shao, YuanWei; Yu, Ming (Frontiers in Neurology, 2023)
Objective Factors that predict poor outcomes in patients with single subcortical infarction (SSI) may differ from those that predict poor outcomes in the SSI subgroup with neurological deterioration (ND). This study aimed to investigate the effect of ND on functional outcomes in patients with SSI and the clinical factors that predict poor outcomes in patients with SSI with ND (SSI-ND) and in all patients with SSI. Methods Patients with SSI were consecutively enrolled in this study. ND was defined as an increase of ≥2 points in the National Institutes of Health Stroke Scale (NIHSS) total score, an increase of ≥1 point in the NIHSS subscore of consciousness or motor function, or any new neurological deficit. Results A total of 255 patients were enrolled, and nine (3.53%) were lost to a follow-up. ND [adjusted relative risk (aRR) = 1.37, 95% confidence interval (CI) = 1.22–1.55, p < 0.001], female sex (aRR = 1.13, 95% CI = 1.03–1.24, p = 0.12), initial NIHSS (aRR = 1.08, 95% CI = 1.07–1.10, p < 0.001), and parental arterial disease (PAD) (aRR = 1.16, 95% CI = 1.07–1.26, p = 0.038) were associated with a poor 90-day outcome (the modified Rankin scale (mRS) > 2 points) in patients with SSI. In the SSI-ND subgroup, PAD (aRR = 2.15, 95% CI = 1.20–3.86, p = 0.01), glycosylated hemoglobin (aRR = 1.17, 95% CI = 1.01–1.35, p = 0.035), and severe NIHSS (aRR = 1.15, 95% CI = 1.06–1.25, p = 0.001) were predictive of a poor outcome, and PAD (aRR = 1.87, 95% CI = 1.19–2.95, p = 0.007) was correlated with higher/worsened NIHSS [> 2 points (median)]. For predicting poor outcomes in patients with SSI-ND with PAD, a more severe NIHSS (aRR = 1.09, 95% CI = 1.02–1.17, p = 0.01) was the only determinant, with a cutoff of 4.5 points, a sensitivity of 94.0%, and a specificity of 83.3%. Conclusions ND is an independent predictor of poor outcomes in patients with SSI, and poor outcome determinants in the SSI-ND subgroup and in all patients with SSI are not identical. For patients with SSI-ND, PAD could aggravate ND and was therefore an essential predictor of poor outcomes.